STUDI KUALITATIF WAJIB PAJAK ORANG PRIBADI PENGUSAHA TERTENTU UNTUK MELAKUKAN PEMBAYARAN PAJAK PENGHASILAN (PPh) (Studi Kasus Pada Pelaku Social Commerce) - Puspawati, Dewita (Riset Akuntansi dan Keuangan Indonesia, 2016)
The purpose of this study was to determine the condition of knowledge of the perpetrators of social commerce as taxpayers specific employers to pay income tax on their business. The determination of the behavior of agents of social commerce when faced with the challenges to pay income tax, and how the constraints faced by the tax officer over tax collection social commerce transactions. This study is a qualitative study conducted by interviewing the perpetrators of social commerc. Interviews showed that the main factor of social commerce offender does not pay income tax is the lack of information if they are taxpayers and are required to pay taxes on the received income. They need have a clear criteria of social commerce taxation, payment term, and the certainty that they are not harmed. Various constraints faced by the tax office for tax purposes social commerce transactions also occur, such as the difficulty to track who transactors social commerce, difficulty to determine the tax object (to the digital format), transactions not only in the customs territory of Indonesia.Â Keywords: Social Commerce, PPh, Wajib Pajak, WPOP Pengusaha Tertentu